Effect of spironolactone and benazepril on furosemide‐induced diuresis and renin‐angiotensin‐aldosterone system activation in normal dogs. (13th March 2021) - Adin, Darcy; Atkins, Clarke; Wallace, Gabrielle; Klein, Allison
Abstract: Background: Diuretic braking during furosemide continuous rate infusion (FCRI) curtails urine production. Hypothesis: Renin‐angiotensin‐aldosterone system (RAAS) activation mediates braking, and RAAS inhibition will increase urine production. Animals: Ten healthy purpose‐bred male dogs. Methods: Dogs received placebo, benazepril, or benazepril and spironolactone PO for 3 days before a 5‐hour FCRI (0.66 mg/kg/h) in a 3‐way, randomized, blinded, cross‐over design. Body weight (BW), serum creatinine concentration (sCr), serum electrolyte concentrations, PCV, and total protein concentration were measured before PO medications, at hours 0 and 5 of FCRI, and at hour 24. During the FCRI, water intake, urine output, urine creatinine concentration, and urine electrolyte concentrations were measured hourly. Selected RAAS components were measured before and after FCRI. Variables were compared among time points and treatments. Results: Diuretic braking and urine production were not different among treatments. Loss of BW, hemoconcentration, and decreased serum chloride concentration occurred during FCRI with incomplete recovery at hour 24 for all treatments. Although unchanged during FCRI, sCr increased and serum sodium concentration decreased at hour 24 for all treatments. Plasma aldosterone and angiotensin‐II concentrations increased significantly at hour 5 for all treatments, despite suppressed angiotensin‐converting enzyme activity during benazepril background treatment. Conclusions: The neurohormonal profile during FCRI supports RAAS mediation of diuretic braking in this model. Background treatment with benazepril with or without spironolactone did not mitigate braking, but was well tolerated. Delayed changes in sCr and serum sodium concentration and incomplete recovery of hydration indicators caused by furosemide hold implications for clinical patients.